Basic electricity (Sterling Book House, 2009)
This expanded and revised U.S. Navy training course text provides thorough coverage of the basic theory of electricity and its applications. It is unquestionably the best book of its kind for either broad or more limited studies of electrical fundamentals. It is divided into 21 chapters and an extensive section of appendixes. Chapters cover safety, fundamental concepts of electricity, batteries, series direct-current circuits, network analysis of direct-current circuits, electrical conductors and wiring techniques, electromagnetism and magnetic circuits, introduction to alternating-current electricity, inductance, capacitance, inductive and capacitive reactance, fundamental alternating-current circuit theory, direct-current generators, direct current motor magnetic amplifiers, and synchros and servomechanisms. Appendixes acquaint lay readers with common terms, abbreviations, component color-code, full load currents of motors, and cable types; they also supply trig functions, square and square roots, basic formulas, and laws of exponents. Thus the reader is supplied with a complete basic coverage of all important aspects of electricity. And, drawing on its ample funds, the Navy was able to fill this text with dozens of illustrations so that the book becomes almost a multimedia teaching process. This is an excellent text for classroom use or for home study. Students will also find it a valuable supplement to courses in which theory is emphasized while little attention is paid to application; it will also supplement a course in which this situation is reversed. In addition, Basic Electricity serves the lay reader who simply wants a knowledge of fundamental concepts of electricity or wishes to study more advanced concepts and applications. 1969 edition.